The Physicochemical and Sensory Evaluation of Seaweed Jam with Various Palm Sugar - Sabarudin, Syahira Anisha; Faridah Kormin (Enhanced Knowledge in Sciences and Technology, 2024)
Gracilaria changii, a red seaweed species recently discovered in Muar, Johor, offers a rich blend of essential nutrients. Various palm sugar varieties, including gula apong, gula melaka, and gula kabong, exhibit a glycemic index below 55, signifying their ability to hinder and control the elevation of blood glucose levels. Furthermore, by fostering a sense of satiety and curbing hunger, these palm sugars may contribute to appetite suppression, supporting weight management efforts and mitigating the risk of obesity. In recent years, more consumers are paying attention to the nutritional value and quality of food products due to increased concern regarding human health problems. The objective of this study was to optimize seaweed jam formulation from red seaweed with three types of palm sugar using a simple lattice mixture design. The optimum formulation was sample 4, which consists of 50% gula apong and 50% gula melaka. The sensory evaluation test for sample 4 was analyzed using a 9-point Hedonic rating scale and was the most acceptable with a test score of 7. The physicochemical properties of seaweed jam were analyzed, where high moisture content was obtained for all samples, low total soluble solid for every sample, pH for seaweed jam was standardized into 3.9, and firmness of each jam differed due to the different palm sugar used. Sample 4 has a lower glycemic index, which is 37. As for the nutritional composition for sample 4, it has low fat content and high energy level. In summary, sample 4 is a novel formulation crafted with various palm sugars. It boasts highly acceptable sensory, favorable physicochemical properties, and a nutrient-rich composition.